Knee degeneration in concrete reinforcement workers. Issue 2 (May 1983) - Wickström, G; Hänninen, K; Mattsson, T; Niskanen, T; Riihimäki, H; Waris, P; Zitting, A
Abstract : The loads on the knees in concrete reinforcement work and maintenance painting were analysed on eight construction work sites. A total of 352 reinforcement workers and 231 painters. Finnish men aged 20-64, were clinically and radiologically examined to determine the condition of the knee joints in active workers. The loads on the knees and the occurrence of minor injuries and accidents were higher in reinforcement work than in painting, but the occurrence of symptoms, clinical signs, and radiological findings was equally common in both groups. Reinforcement work seemed to provoke more symptoms from degenerated knees than painting.